Posttransplant Soluble B-Cell Activating Factor Kinetics in Pediatric Recipients of First Kidney Allograft. Issue 1 (January 2015) - Comoli, Patrizia; Quartuccio, Giuseppe; Cioni, Michela; Parodi, Angelica; Nocera, Arcangelo; Basso, Sabrina; Fontana, Iris; Magnasco, Alberto; Sioli, Viviana; Guido, Ilaria; Klersy, Catherine; Zecca, Marco; et al.
<x xml:space="preserve">Abstract</x> Background Development of de novo donor-specific antibodies (dnDSA) is associated with late or chronic antibody-mediated rejection (CAMR) and poor graft outcome in low-risk kidney transplant recipients. High-level soluble B-cell activating factor (sBAFF) was observed in kidney recipients at higher risk of developing dnDSA. Methods We longitudinally analyzed sBAFF levels in 81 consecutive primary pediatric kidney recipients monitored for de novo human leukocyte antigen (HLA) antibody (Ab) occurrence to gain insight into the events conditioning B-cell activation posttransplant and to analyze the usefulness of paired DSA-sBAFF monitoring in this clinical setting. Results At a median follow-up of 65 months, 23 patients (28%) developed dnDSA, with 13 of 23 developing CAMR. Irrespective of HLA Ab status, sBAFF levels progressively increased in all patients in the first posttransplant year, thereafter reaching a plateau. sBAFF levels were influenced by the degree of HLA class I antigen match and donor age. Despite higher levels of sBAFF in HLA Ab-positive patients (median and 95% confidence interval sBAFF in DSA+non-DSA patients: 568, 534–608 pg/mL vs. 502, 422–548 pg/mL in Ab-negative patients; P<0.05), we found that sBAFF monitoring could not predict DSA development by a time to event longitudinal analysis. Moreover, sBAFF kinetics up to CAMR onset could not anticipate CAMR development in the DSA cohort. Conclusion Our findings provide evidence of early posttransplant B-cell activation even in unsensitized recipients of first kidney allograft. The significance of this activation, likely induced by exposition to the allograft, is yet unclear.